A Fractional-Order Electro-Thermal Aging Model for Lifetime Enhancement of Lithium-ion Batteries. Issue 2 (2018) - Mohajer, Sara; Sabatier, Jocelyn; Lanusse, Patrick; Cois, Olivier
Abstract: This paper proposes a battery model for the application of automotive battery management systems. The fractional-order electrical battery model simulates the voltage response to the input current. In addition, the undesired side reactions have been taken into account to model the degradation mechanisms leading to loss of battery performance. The thermal behavior is also modeled by using lumped-parameter method. The three above-mentioned sub-models have been coupled to form an electrothermal aging battery model. Validation tests have been performed to justify the accuracy of the model. A novel approach for aging modeling is proposed, based on decoupling of calendar and cycling effects. Respective aging maps have been obtained and compared to the aging measurements. This model can be used as a basis for improvement of battery lifetime specially during aggressive fast charging.